Nonlinear analysis of FGM plates using generalised higher order shear deformation theory. (27th June 2019) - Srividhya, Singam; Kumar, Basant; Gupta, R.K.; Rajagopal, Amritham
In the present work a generalised higher order shear deformation theory (GHSDT) for the flexural analysis of the functionally graded plates subjected to uniformly distributed load of varying intensities has been formulated. A finite element formulation with a confirming type isoparametric approximation has been formulated and implemented. Various types of boundary conditions have been considered for the analysis. The formulation accounts for geometric nonlinear terms in the strains. The formulation also complies with plate surface boundary conditions and does not require shear correction factors. The formulation has been validated by comparing the results with those available in the literature. Numerical results for different load parameters, volume fraction, and boundary conditions have been presented and compared with literature. Results show that the proposed GHSDT gives a better approximation to transverse shear strains and the results are closer to those obtained from analytical solutions.